MENINGKATKAN KESADARAN DALAM BERWIRAUSAHA MELALUI POTENSI HASIL PANEN (MIE TOMAT) - Persada, Andhika Giri (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
The majority of people in Indonesia live in the village. Not a few people of Indonesia who came from the village leaving the village to find a decent job in the city. This thought is certainly one, but a deserted village has the potent ial to move forward. Crops and livestock in abundance will be very profitable if managed correctly. For the welfare of rural communities, it takes training that is to grow the ability of rural communities. Creativity and innovation in managing crops and livestock to be of high economic value is needed. One way for the welfare of rural communities is to provide entrepreneurial training and explanation. Entrepreneurship is a process of doing something creative and new or different (innovative) are useful in providing more value. Gejayan hamlet located in Pakis subdistrict, Magelang is a hamlet whose majority are farmers. Yields are the largest of Hamlet Gejayan tomatoes. Because tomatoes are abundant harvest, the price of tomatoes to be very low. Many farmers are losing money due to the gains a bit. It takes innovation in managing tomatoes are abundant. Tomato noodles are noodles that uses the basic ingredients of tomatoes. In the field of health noodles consumed tomatoes better than the noodles instant noodles are sold in Indonesia. Tomato noodle products were also given the attractive packaging to attract consumers. With the tomato noodle products, is expected to improve the local economy Gejayan Hamlet.